The integration of lean manufacturing and ergonomics approach in workplace design - Yusoff, Sabariah Mohd (2013)
In today’s business environment, every company compete aggressively to increase their level of productivity. Workplace design can be significantly affected the level of productivity, as it is based and carried out by using lean concepts and Ergonomics principles. The aim of this paper is, ideally, to propose integration of these concepts for the designing of workplaces. These ideas come out when normally company just focused into one approach, either Lean or Ergonomics. Through this, we hope that the manufacturing sector can get an optimized design of the workplaces. Lean Manufacturing systems had argued that by implementing Lean systems it is possible to obtain a decrease in the waste in manufacturing while Ergonomics can increase the workers’ comfort. Both of these can lead to an increase on the productivity level.